International Indigenous University - Montes, Claudine (Revista de Estudos em Relações Interétnicas | Interethnica, 2013)
The purpose of this paper is to get responses and feedback on the ideas as they stand thus far regarding an International Indigenous University or IIU. The IIU is in no way ready to get off of the ground and the paper has no committment with any nation to do any work yet. The ideia is to that areas the paper might have overlooked will be spotted by others who have similar interests. Also I am hoping to see what kind of interest is out there in this type of project. I have much more written, in detail about IIU, but it is not appropriate for the length restrictions of this arena.